2022
DOI: 10.3390/jcm11175176
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride–Glucose Index May Predict Renal Survival in Patients with IgA Nephropathy

Abstract: Background: The triglyceride–glucose (TyG) index is a simple, novel and reliable surrogate marker of insulin resistance. However, evidence for the prognostic impact of an elevated TyG index on IgA nephropathy (IgAN) is limited. Therefore, we evaluated the relationship between the TyG index and the risk of renal progression in IgAN. Method: This cohort study involved biopsy-proven IgAN between January 2009 and December 2018 in West China Hospital, in which patients were assigned to two groups based on the cut-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A major finding of our study was that an elevated TyG index, a surrogate marker of IR, is significantly associated with a higher risk of ESRD in individuals with T2DM and CKD. It was suggested that the TyG index appeared to be associated with incident CKD ( 21 24 , 40 ) and CKD progression ( 25 , 41 ) in patients with or without diabetes. Recently, Fritz et al.…”
Section: Discussionmentioning
confidence: 99%
“…A major finding of our study was that an elevated TyG index, a surrogate marker of IR, is significantly associated with a higher risk of ESRD in individuals with T2DM and CKD. It was suggested that the TyG index appeared to be associated with incident CKD ( 21 24 , 40 ) and CKD progression ( 25 , 41 ) in patients with or without diabetes. Recently, Fritz et al.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of IR is increasing rapidly worldwide due to the aging population, obesity, and physical inactivity [11] . Increasing evidence has shown that IR may act as a critical mechanism of renal damage [7,19] . Previous studies have found that IR existed in different stages of CKD, even in the early stage of mild renal function damage [7,20,21] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the TyG index was highly sensitive (96.5%) and speci c (85.0%) for the detection of IR, compared to the hyperinsulinemiceuglycemic clamp technique [12] . Furthermore, research has shown that the TyG index performed better than HOMA-IR for the estimation of IR [26] , and was associated with severe clinical pathological manifestations [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the association between the TyG index and renal damage in different populations 23–29 . However, there has been a limited focus on hypertensive cohorts 28,29 .…”
Section: Discussionmentioning
confidence: 99%